DOROTHY SMITH'S SOCIAL SCIENCE APPROACH AND INSTITUTIONAL ETHNOGRAPHY - Oztan, Ece (ISTANBUL UNIV, METHODOLOGY & SOCIOLOGY RESEARCH CENTER, 2013)
This article examines the methodological and theoretical basis of the institutional ethnography approach introduced by Canadian sociologist Dorothy E. Smith. Institutional ethnography refers to the empirical investigation of linkages within the local context of everyday world organizations and the trans-local process of governance. For institutional ethnography, the everyday world is the material context of each embodied subject. The works done by each embodied subject in everyday life is just a starting point for institutional ethnography. The notion of institution indicates the clusters of text mediated relations organized around specific functions such as education or welfare. Smith proposes institutional ethnography as a part of an empirically strong alternative methodology and as a politically empowering research strategy. This approach combines Marx's materialist method with ethnomethodology, feminist standpoint theory and Foucauldian discourse theory. This article shows how institutional ethnography links micro and macro settings by giving empirical examples and compares it with some other qualitative research approaches such as the extended case method by Burawoy or feminist standpoint theory.
Keywords: Institutional Ethnography; Methodology; Feminist Methodology; GENDER; RACE; Sociology